The Influence of Brand Experience Towards Brand Trust on New Entry Sport Product - Antonius Alijoyo, Franciskus; Novita Puri, Farisa (Journal of World Science, 2023)
The purpose of this research is to determine the impact of brand experience towards brand trust, particularly in new entry products with the new entry product in the sports industry as a proxy, particularly in golf balls. The objective of this study is to research how a new entry product (in the sports market) could gain its brand trust based on its brand experience. This research collected and analyzed using numerical data through questionnaires and a total of 87 responses were considered valid for data analysis using SPSS. The hypothesis testing is done using linear regression, using brand experience as independent variable and brand trust as dependent one. The result shows that there is a linear correlation and positive influence from brand experience towards brand trust in the new entry golf product. Thus, it could be concluded that brand experience, especially in new entry products, is essential, since it could lead to customer trust towards the brand. Impllication of this research is findings emphasize the significance of brand experience as a driver of brand trust for new entry products. This suggests that companies entering competitive markets should prioritize creating positive brand experiences to establish trust among consumers. Managers can now tailor their strategies to enhance brand experiences, ultimately boosting brand trust and customer loyalty.